Identification of Gender-Specific Molecular Differences in Glioblastoma (GBM) and Low-Grade Glioma (LGG) by the Analysis of Large Transcriptomic and Epigenomic Datasets - Khan, Md Tipu; Prajapati, Bharat; Lakhina, Simran; Sharma, Mridula; Prajapati, Sachin; Chosdol, Kunzang; Sinha, Subrata (Frontiers in Oncology, 2021)
Gender based differences in the incidence and behaviour of glioma are well known. The incidence of glioma is higher in males than females, the difference being more striking for Glioblastoma Multiforme (GBM) than Low Grade Glioma (LGG). Females also respond better to standard therapy. However, the molecular basis for these differences is not well understood. Here, we have analysed data from publically available databases to identify molecular indicators for these gender based differences. Different databases, particularly TCGA GBM and LGG transcriptomic and epigenetic data were used to identify differentially expressed and methylated genes in males and females. We performed weighted correlation network analysis (WGCNA), to identify clusters of highly correlated genes (modules) in both genders. Further, the gene sets that form significant differential networks and their ontological features were identified from these modules. There was a differential gender based influence of several genes on survival. Also, the autosomal genes FGF13, PPP2R2C, LANCL3, FRG1BP, LINC00632, TCEAL6 AND NOX5 and Synapsin 1(X-linked) had differential DNA methylation and expression profile in male and female GBM, while for LGG, the genes were SCML2, SLITRK4 and EGFL6. Network analysis, followed by ontology, has also shown several pathways, including the WNT pathway to be having differential connectivity in male and female samples. Our study identifies several crucial differences between male and female glioma, which could be subjects for further studies. It also highlights that molecular studies without consideration of gender can obscure critical elements of biology and highlights the importance of parallel but separate analyses of male and female patients.